Engineering zinc oxide hybrid selenium nanoparticles for synergetic anti-tuberculosis treatment by combining Mycobacterium tuberculosis killings and host cell immunological inhibition - Lin, Wensen; Fan, Shuhao; Liao, Kangsheng; Huang, Yifan; Cong, Yanguang; Zhang, Junai; Jin, Hua; Zhao, Yi; Ruan, Yongdui; Lu, Hongmei; Yang, Fen; Wu, Changxian; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction As a deadly disease induced by Mycobacterium tuberculosis (Mtb), tuberculosis remains one of the top killers among infectious diseases. The low intracellular Mtb killing efficiency of current antibiotics introduced the long duration anti-TB therapy in clinic with strong side effects and increased drug-resistant mutants. Therefore, the exploration of novel anti-TB agents with potent anti-TB efficiency becomes one of the most urgent issues for TB therapies. Methods Here, we firstly introduced a novel method for the preparation of zinc oxide-selenium nanoparticles (ZnO-Se NPs) by the hybridization of zinc oxide and selenium to combine the anti-TB activities of zinc oxide nanoparticles and selenium nanoparticles. We characterized the ZnO-Se NPs by dynamic laser light scattering and transmission electron microscopy, and then tested the inhibition effects of ZnO-Se NPs on extracellular Mtb by colony-forming units (CFU) counting, bacterial ATP analysis, bacterial membrane potential analysis and scanning electron microscopy imaging. We also analyzed the effects of ZnO-Se NPs on the ROS production, mitochondrial membrane potential, apoptosis, autophagy, polarization and PI3K/Akt/mTOR signaling pathway of Mtb infected THP-1 macrophages. At last, we also tested the effects of ZnO-Se NPs on intracellular Mtb in THP-1 cells by colony-forming units (CFU) counting. Results The obtained spherical core-shell ZnO-Se NPs with average diameters of 90 nm showed strong killing effects against extracellular Mtb, including BCG and the virulent H37Rv, by disrupting the ATP production, increasing the intracellular ROS level and destroying the membrane structures. More importantly, ZnO-Se NPs could also inhibit intracellular Mtb growth by promoting M1 polarization to increase the production of antiseptic nitric oxide and also promote apoptosis and autophagy of Mtb infected macrophages by increasing the intracellular ROS, disrupting mitochondria membrane potential and inhibiting PI3K/Akt/mTOR signaling pathway. Discussion These ZnO-Se NPs with synergetic anti-TB efficiency by combining the Mtb killing effects and host cell immunological inhibition effects were expected to serve as novel anti-TB agents for the development of more effective anti-TB strategy.